P185 A comparison of early response parameters to inform a treat-to-target approach in ulcerative colitis. (15th January 2020) - Dulai, P; Feagan, B; Sands, B; Lasch, K; Lirio, R; Feng, D
Abstract: Background: We aimed to evaluate early markers of response after vedolizumab (VDZ) induction therapy for their prognostic value in determining the long-term risk of colectomy. Methods: Post hoc analysis of VDZ-treated patients ( n = 588) enrolled in the GEMINI 1 and long-term safety (LTS) clinical trial programs. Rates of colectomy during the 7-year follow-up period were compared according to treatment response status at week 6 (induction) for various definitions of Clinical remission [CR] (rectal bleeding sub-score [RBS] 0 + stool frequency sub-score [SFS] ≤1), Biomarker remission [BR] (faecal calprotectin [FC] ≤50, ≤100, ≤250), or endoscopic improvement [EI] (Mayo endoscopic sub-score [MES] ≤1) and endoscopic remission [ER] (MES 0). Time-to-event with log-rank and Cox proportional hazard analyses were used and presented as hazard ratios (HR) with 95% confidence intervals (CIs). Results: The risk of colectomy was comparable between UC patients achieving week 6 CR vs. those with persistent symptoms (HR 0.74, 95% CI 0.37–1.48, p = 0.39). The risk of colectomy trended lower in patients achieving week 6 EI (HR 0.55, 95% CI 0.28–1.10, p = 0.08), but was comparable between those achieving an MES of 1 vs. 0 (HR 1.45, 95% CI 0.39–5.48, p = 0.58). The risk of colectomy was significantly lower in patients achieving week 6 BR using an FC cut-off of 250 (HR 0.30, 95% CI 0.13–0.68, p = 0.002) and 100 (HR 0.18, 95% CI 0.04–0.73, p = 0.007) but not with a cut-off of 50 (HR 0.34, 95% CI 0.08–1.41, p = 0.12). The proportion of patients requiring colectomy over a 7-year period was lower among those achieving week 6 BR (FC 250, 3.3%; FC 100, 1.8%) compared with patients who achieved week 6 EI (5.6%), although over one-third of patients who achieved week 6 BR had moderate–severe endoscopic activity (MES 2–3) at week 6. Conclusion: FC as an early biomarker of response at week 6 may aid in identifying patients who remain at low risk of future colectomy, despite having persistent symptomatic or endoscopic activity. These findings may be limited by overall low rates of colectomy in GEMINI LTS, but can inform considerations for early treat to target approaches.